IMAGE ENCRYPTION ALGORITHM USING TWO-DIMENSIONAL CHAOTIC MAPS - A. V. Sidorenko; I. V. Shakinko; Yu. V. Sidorenko (Системный анализ и прикладная информатика)
A new image encryption algorithm based on dynamic chaos is proposed. The encryption is performed using the modified element permutation procedure. The element value changing procedure is carried with regard to the performed permutation. The modified permutation procedure includes the following steps: (1) permutation table creation; (2) permutation of image blocks, (3) element permutation in the image regions. The procedure «block permutations – permutation in the image regions» is performed q times – for this study q = 3. The second element value changing procedure is realized with the use of the pseudorandom sequence G that is added to the image elements. The following algorithm is proposed for the formation of this pseudorandom sequence: (1) the formation of the sequence G element distribution by brightness; (2) sequence G element initialization; (3) permutation of the sequence G elements. It is shown that, owing to the modified permutation procedure, the amount of calculations for new positions of the elements using chaotic maps is reduced by a factor of a – in this study a is equal to 16 and 64. The implementation of the proposed element value changing procedure necessitates the formation of d pseudorandom values from the interval [0, 1) with a uniform distribution. Actually, for the majority of practical cases d = 256 is applicable. The proposed algorithm has been tested as follows. The correlation coefficients have been computed for the original and encrypted images, and also for the adjacent elements in the vertical, horizontal, diagonal directions. The algorithm key sensitivity has been evaluated. Besides, the values of the unified average change intensity (UACI) and the ratios of differing bits to the total number of bits have been determined. As demonstrated by the testing results, the proposed algorithm is highly operable and may be successfully used to solve the tasks of information security.